Implementation of EU Climate and Energy Policy Goals in the Context of the Energy Policies of Chosen Member States - Zajączkowska, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The main aim of this article is to present the results of the analysis of the EU climate and energy policy goals in selected Member States in the context of their energy policies. The analysis covers the period 2008–2014 and focuses on seven EU Member States: the Czech Republic, Denmark, Germany, France, Lithuania, Poland and the United Kingdom. Each of the countries is implementing EU climate and energy policy goals, but to varying degrees. The research leads to the conclusion that more and more countries implement energy policy primarily based on national policy, which is not always consistent with the assumptions of the EU’s policy.